Nurses' Moral Experiences with End-Of-Life Care in a Community Hospital Intensive Care Unit - Wong, Sandra Mei Yun (Université d'Ottawa / University of Ottawa, 2018)
Extant literature has identified how nurses perceive their role and their experience of providing end-of-life care (EOLC) in intensive care units (ICUs). However, there is an empirical gap in what is known about nurses’ provision of EOLC in ICUs of community hospitals and in particular, their moral experiences in the provision of care. Using Thorne’s (2008) Interpretive Description (ID), this study was designed to explore nurses’ moral experiences in providing EOLC in an ICU of a large community hospital. Face-to-face, semi-structured, interviews were conducted with seven nurses who have had experience providing care to dying patients in an ICU of a large community hospital. Findings of the study revealed an overarching theme of “switching gears”, which reflected the moral experiences of the participants as they shifted the focus of their identity and their responsibilities from saving lives to caring for dying patients. The shift in focus included participants being involved with “making a patient palliative”, “providing dignity conserving care”, and “supporting families”. Yet, participants encountered many “struggles” embedded in the community hospital ICU context that made it difficult for them to “switch gears”. These “struggles” included frequent transfers of dying patients out of the ICU, heavier patient assignments, and the multiple roles and responsibilities assumed by participants. This study enhances our knowledge and understanding about ICU nurses’ identity, especially what they take responsibility for in the care of dying patients and their families. Furthermore, the study findings highlight the specific challenges nurses encounter in the community ICU context, while providing EOLC to patients and families. These findings bring about important implications to nursing practice, education and research.
Keywords: End-of-life care; Community Hospital; Ethics; Nursing; Critical Care